Efficacy of virtual reality exposure therapy for the treatment of dental phobia in adults: A randomized controlled trial. (March 2019) - Gujjar, Kumar Raghav; van Wijk, Arjen; Kumar, Ratika; de Jongh, Ad
Highlights: VRET seems to be an effective treatment for dental phobia. Six months after VRET, 85% of patients had lost their dental phobia diagnosis. Majority of the patients scheduled dental appointments within 6-months post-VRET. Advantage of VRET is that it can be carried out by trained auxiliary personnel. Abstract: Background: Although Virtual Reality Exposure Therapy (VRET) has proven to be effective in the treatment of various subtypes of specific phobia, there is limited evidence of its role in the treatment of dental phobia. Method: A single-blind RCT was conducted among 30 randomized patients with dental phobia to either VRET or informational pamphlet (IP) condition. Primary outcome anxiety measures (VAS-A, MDAS and DFS) were evaluated at baseline, pre- and post-intervention, 1-week, 3-months and 6-months follow-up. Secondary outcome measures assessed were pre-post behavioral avoidance, temporal variations of heart rate and VR-experience during and post-VRET, and dental treatment acceptance in both conditions at 6-month follow-up. Results: Intention to treat analysis, using a repeated measures MANOVA, revealed a multivariate interaction effect between time and condition (p = 0.015) for all primary outcome measures (all ps < 0.001). Only patients of the VRET condition showed a significant reduction in anxiety scores (mean reduction [s.d.]: VAS-A 44.4 [36.1]; MDAS 7.1 [5.4]; DFS 21.2 [13.1]) whereas the patients in the IP group did not (mean reduction [s.d.]: VAS-A −0.33 [7.7]; MDAS −0.33 [1.3]; DFS −1.9 [3.8]), F (15, 14) = 3.3, p = 0.015. Conclusions: VRET was found to be efficacious in the treatment of dental phobia.